Emerging from the Mist: French Universities and Global Rankings - Highman, Ludovic (International Higher Education, 2021)
The French higher education landscape has been considerably altered in the early twenty-first century. In order to enhance the competitiveness of the sector at the global level, the French government has steered the system through structural policy processes aimed at consolidating it and overcoming the traditional divide between universities and grandes écoles, while providing incentive schemes rewarding mergers.